No association of ABO blood groups and Rh factor with primary liver cancer in cirrhotic patients: a single-center cross-sectional study - Dong, Liyan; Yin, Yuhang; Lu, Huiyuan; Sun, Di; Wang, Dongyang; Zou, Deli; Qi, Xingshun (Frontiers in Medicine, 2025)
Background Primary liver cancer (PLC) is one of the most common cancers worldwide. ABO blood groups and rhesus (Rh) factor are inherited characteristics. Their association with the presence of PLC remains unclear in cirrhotic patients. Hence, the purpose of this cross-sectional study was to evaluate whether blood groups were risk factors for the presence of PLC in cirrhosis. Methods Patients with liver cirrhosis who were consecutively admitted to the Department of Gastroenterology of the General Hospital of Northern Theater Command from 1 January 2010 to 30 June 2014 were retrospectively screened. Logistic regression analyses were performed to explore the association of ABO blood groups and Rh factor with PLC in cirrhotic patients. Adjusted odds ratios (aORs) with 95% confidence intervals (CIs) were calculated after adjusting for gender, age, family history of liver cirrhosis, HBV-DNA positivity, and etiology of cirrhosis. Subgroup analyses were performed according to the etiology of liver cirrhosis. Results Overall, 1,158 cirrhotic patients without PLC and 240 cirrhotic patients with PLC were included in the study. After adjusting for confounding factors, non-O (aOR = 0.763; 95%CI = 0.449–1.298, p = 0.319), A (aOR = 0.643; 95%CI = 0.332–1.246, p = 0.191), B (aOR = 0.835; 95%CI = 0.453–1.540, p = 0.564), AB (aOR = 0.888; 95%CI = 0.363–2.170, p = 0.795), and Rh (+) (aOR = 0.239; 95%CI = 0.036–1.571, p = 0.136) blood groups were not independently associated with PLC in cirrhotic patients. In the subgroup analysis of HBV-related cirrhotic patients, the proportion of A blood group was significantly lower in cirrhotic patients with PLC than in those without PLC (24.17% vs. 33.99%, p < 0.001); however, in HCV- and alcohol-related cirrhotic patients, the proportions of ABO blood groups and Rh factor were not significantly different between the two groups. Conclusion ABO blood groups and Rh factor may not be associated with the presence of PLC in cirrhotic patients.